Cognitive Dependency on Clinical Decision Support Systems: Implications for Diagnostic Reasoning - Hayati, Zahratul; Yaman, Imran; Sya'diah, Yayah (Asian Journal of Healthcare Analytics, 2026)
The development of artificial intelligence-based Clinical Decision Support Systems (CDSS) has transformed the diagnostic decision-making process in modern health practice. Although CDSS is capable of improving clinical efficiency and accuracy, overuse has the potential to lead to cognitive dependency and automation bias that can affect the quality of medical personnel's diagnostic reasoning. This article aims to conceptually analyze the implications of dependence on CDSS on critical thinking processes and clinical decision-making. The study was conducted through a review of the latest literature in the field of health informatics and behavioral decision-making. The results of the analysis show that CDSS acts as an effective cognitive augmentation tool when used proportionally, but can weaken analytical evaluation if used without critical reflection. An implementation approach that emphasizes a balance between technological support and the professional autonomy of health workers is needed to maintain the integrity of diagnostic reasoning in the digital age.